Rheumatoid arthritis seems to have DMARD treatment decision influenced by fibromyalgia - Chakr,Rafael Mendonça da Silva (2017)
Abstract Objective: To compare DMARD use in patients with and without FM over time, including overtreatment and undertreatment rates in both groups. Methods: A prospective cohort study with patients attending an RA outpatient clinic was conducted. Participants were consecutively recruited between March 2006 and June 2007 and were followed through December 2013. Data on DMARD use (prevalences, doses and escalation rates), DAS28, HAQ and radiographic progression were compared among RA patients with FM and without FM. Mistreatment clinical scenarios were allegedly identified and compared between groups. Results: 256 RA patients (32 with FM) were followed for 6.2 ± 2.0 (mean ± SD) years comprising 2986 visits. At baseline, RA duration was 11.1 ± 7.4 years. DAS28 and HAQ were greater in RA with FM group, and were closer to RA without FM group towards the end. RA patients with FM used higher doses of tricyclic antidepressants, leflunomide and prednisone, and lower doses of methotrexate. When compared to RA patients without FM, participants with RA and FM used more often tricyclic antidepressants, leflunomide, prednisone, continuous analgesics and less often methotrexate. Groups presented similar 7-year biologic-free survival, and radiographic progression-free survival in Cox regression. RA patients with FM had greater proportions of visits in mistreatment scenarios when compared to RA patients without FM (28.4 vs. 19.8%, p < 0.001). Conclusions: RA patients with FM used more leflunomide and prednisone, and RA mistreatment was more frequent in FM patients. Certainly, RA patients with FM will benefit from a personalized T2T strategy, including ultrasound (when suitable) and proper FM treatment.